New insights on the psammophilic gradient applying a multidisciplinary biogeochemical based approach - a case study in the Mediterranean Region of the Portuguese coast - Pereira, Marizia (2012)
From the point of view of plant life, the communities of recent coastal beaches and sand dunes (with ages inferior to 4000 years B. P.) are submitted to a stressful and harsh environment, generally characterized by incipient or inexistent pedogenetic evolution of the oligotrophic sands, weak water retention capacity and total absence of podzolization. In the biogeographical Mediterranean Region of the Portuguese coast, the climatic conditions are also severe. Major features are hot and long summers, short winters, low and concentrate precipitation patterns, weak incidence of aestival fogs, and increasing temperatures in the South. The unique spatial position of interface between the sea and land, and consequent environmental extreme conditions, result in original, sensitive, and valuable habitats, distributed along a well marked littoral-inland psammophilic gradient. This vegetation shows a notorious succession of segregated communities, (geopermasig-metum), that follows a clear geomorphological zonation (embryonic, primary and semi-stabilized dunes). The thermophilic conditions, the sea salt influence, the wind, the mobility of the sand, the waves action and the oligotrophic conditions, determine the occurrence of specific and highly adapted plant associations, confinedto that specific type of habitat, having few species in common with other terrestrial ecosystems. Specialized in relatively spatially isolated and low sized communities, they are endowed with important ecological services and high interest for conservation.